PENGARUH PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH MELALUI PENDEKATAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR BIOLOGI SISWA SMA YPPK ST. THOMAS WAMENA - PARURA, HANA; SIMBIAK, MAIKEL (Jurnal Ilmu Pendidikan Indonesia, 2018)
The objectives of this research are : (1) The influence application of the learning based problem through guidance to the ablity of the student critical think at the main biodiversity. (2) The influence application of the learning based problem through guidance to result study at the main biodiversity (3) The raising application of the problem based learning trough approach inquiry guidance to the ablity critical think the result study can be dilentatisme of value n-Gain the result study at the main biodiversity.The population is this observation on the students guide Xa and class Xb. The method which used is the problem based learning at the experiment class and communication method at control class. The plan of this observation is "one group pretest-posttest design". Technic analysis different test with programme SPSS 16. The result of this observation show that : (1) Presence was influence application of the problem based learning trough approach inquiry guidance to the ablity critical think refer to t-test 0,0025<0,05. (2) Presence was influence application of the problem based learning trough the result study with value 0,006<0,05. (3) Presence was raising application of the problem based learning trough approach inquiry guidance to the ablity critical think the result study can be dilentatisme of skor n-Gain the result study at experiment class is 0,63 and at control class is 0,53, value n-Gain the ablity critical think at experiment class is 0,65 and kontrol class is 0,46. Key word : The influence application of the problem based learning , the ablity critical think, the result study.